Dynamics and operation optimization of partial space elevator with multiple climbers. Issue 10 (15th May 2019) - Shi, Gefei; Li, Gangqiang; Zhu, Zhanxia; Zhu, Zheng H.
Abstract: This work studies the dynamics and optimal stabilization method of a partial space elevator (PSE) system with multiple climbers. All satellites and climbers are assumed as lumped masses that are connected by straight, massless, and inextensible tethers. A general dynamic model is derived for the PSE with multiple climbers. It is found different climber moving patterns of climbers have major influence of dynamic behavior of PSE. Optimal control is used to develop optimal operation modes to suppress the libration of PSE with multiple climbers. Moreover, a new operation mode is proposed to approach the desired mission objectives. It is found that all libration angles can be suppressed to zero by the end of the transfer period if two climbers can be kept at a constant speed. At the same time, the magnitudes of libration angles can be kept bounded by regulating the speed of the middle climber relative to other two climbers.